Pneumonia associated with mechanical ventilation: prevention strategies used by the multi-professional team (Research, Society and Development, 2021)
The present study aimed to describe the main strategies for the prevention of ventilator-associated pneumonia by the multidisciplinary team. This is an integrative literature review, where the survey of the study was carried out between May and June 2021, through the VHL, with the aid of the LILACS, BEDENF, SCIELO and MEDLINE databases. The Health Sciences Descriptors (DeCS) being used: Pneumonia associated with mechanical ventilation; Prevention of diseases; and Patient Care Team. After the inclusion and exclusion criteria, 13 studies were selected to compose this study. The study was carried out in two categories: Multiprofessional team work and VAP prevention strategies. The study shows the main strategies performed by the multidisciplinary team for the prevention of VAP in hospitalized patients, as well as: daily interruption of sedation; elevation of the head of the bed in 30º-45º; hand hygiene; oral hygiene; control of the ventilatory circuit, cuff pressure and use of Bundles are effective measures for the prevention of VAP. The multiprofessional team needs to work together and be competent to provide adequate care to patients on mechanical ventilation, acting to prevent the risk of infection and possible VAP, always offering quality and safe care. Thus, such strategies can contribute to the advancement of health and reduce the incidence of cases of VAP in patients using MV in the ICU.